Cardiale Erschöpfung durch Übertraining und Langzeitausdauerbelastungen - Altenberger, H.; Baumgartl, P. (Österreichisches Journal für Sportmedizin, 2001)
About functional myocardial changes - known as cardiac fatigue - from long term endurance effort and overtraining.